2016
DOI: 10.1038/nrg.2016.11
|View full text |Cite
|
Sign up to set email alerts
|

Causes of molecular convergence and parallelism in protein evolution

Abstract: To what extent is the convergent evolution of protein function attributable to convergent or parallel changes at the amino acid level? The mutations that contribute to adaptive protein evolution may represent a biased subset of all possible beneficial mutations owing to mutation bias and/or variation in the magnitude of deleterious pleiotropy. A key finding is that the fitness effects of amino acid mutations are often conditional on genetic background. This context dependence (epistasis) can reduce the probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
341
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(343 citation statements)
references
References 127 publications
1
341
1
Order By: Relevance
“…Furthermore, a recent study showed that the frequency of convergent and parallel substitutions in protein-coding genes declines with increasing phylogenetic distance 29 . It was suggested that accumulation of changes in the genomic background can modify epistatic interactions, limiting the opportunities for adaptive homoplasy 29,30 . While that study examined a broad sampling of mammalian diversity, the species included also showed little phenotypic convergence.…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study showed that the frequency of convergent and parallel substitutions in protein-coding genes declines with increasing phylogenetic distance 29 . It was suggested that accumulation of changes in the genomic background can modify epistatic interactions, limiting the opportunities for adaptive homoplasy 29,30 . While that study examined a broad sampling of mammalian diversity, the species included also showed little phenotypic convergence.…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%
“…4; markers [30][31][32][33][34][35][36][37][38][39][40]; three additional diagnostic WSINE1/1a elements present in thylacine and dasyurids but absent in the numbat and outgroup marsupials (Supplementary Fig. 4; markers 26-28); and one marker present in thylacine and numbat but absent in other dasyuromorphs (Supplementary Fig.…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%
“…Another issue concerns genealogical discordance between the phylogeny of the examined species and the phylogenies of the genes that underlie the measured trait (Hahn and Nakhleh, 2016;Storz, 2016a). In comparative studies of Hb evolution involving orthologous genes from a diversity of species, it may often be the case that phylogenies of the α-and ÎČ-globin genes are not congruent with one another or with the assumed species tree Hoffmann et al, 2008a,b;Opazo et al, 2008aOpazo et al, ,b, 2009Runck et al, 2009Runck et al, , 2010Gaudry et al, 2014;Natarajan et al, 2015a).…”
Section: The Importance Of Accounting For Phylogenetic Historymentioning
confidence: 99%
“…Some of the processes enabling C 4 evolution appear to be shared between different lineages Ludwig, 2013), including parallel changes to amino acid sequences (Svensson et al, 2003;Christin et al, 2007Christin et al, , 2008Besnard et al, 2009;Kapralov et al, 2011), common changes to cellspecific expression patterns and regulatory factors John et al, 2014;Williams et al, 2016), and even convergent recruitment of specific gene lineages to the C 4 pathway (Christin et al, 2013(Christin et al, , 2014(Christin et al, , 2015John et al, 2014). The instances of commonality and bias in different C 4 lineages are not surprising, as environmental, anatomical, and metabolic constraints, as well as genome content and structure, limit routes of evolutionary innovation (Weinreich et al, 2006;Christin et al, 2010;Edwards and Donoghue, 2013;Stern, 2013, Storz, 2016. However, understanding the individual molecular mechanisms underlying the above processes and recognizing their similarities and differences are essential for realizing how evolution built different C 4 plants and how we might use this knowledge to construct a functional CO 2 -concentrating mechanism in C 3 crops (von Caemmerer et al, 2012).…”
mentioning
confidence: 99%